2008
DOI: 10.1007/s11947-008-0072-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fermentation Parameters for Higher Lovastatin Production in Red Mold Rice through Co-culture of Monascus purpureus and Monascus ruber

Abstract: Monascus, fermented rice (red mold rice), has been found to reduce the serum total cholesterol and triglyceride due to presence of lovastatin. Lovastatin acts as an inhibitor of 3-hydroxy-3-methyl glutaryl coenzyme A reductase. Coculture of Monascus purpureus MTCC 369 and Monascus ruber MTCC 1880 was used to produce red mold rice by solid-state fermentation. Optimization of different fermentation process parameters such as temperature, fermentation time, inoculum volume, and pH of the solid medium was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 20 publications
3
37
3
1
Order By: Relevance
“…MnSO 4 .7H 2 O, glucose and peptone were found more significant medium components for lovastatin yield with Monascus purpureus (Subhagar et al 2010). Panda et al (2010b) had attempted screening of the nutrients with Plackett-Burman design for lovastatin production and concluded that it was greatly influenced by the concentration of malt extract, (Lopez et al 2003). According to the literature, widely used carbon sources for lovastatin production are lactose, glycerol and glucose.…”
Section: Screening Of Substrates and Nutrientsmentioning
confidence: 99%
“…MnSO 4 .7H 2 O, glucose and peptone were found more significant medium components for lovastatin yield with Monascus purpureus (Subhagar et al 2010). Panda et al (2010b) had attempted screening of the nutrients with Plackett-Burman design for lovastatin production and concluded that it was greatly influenced by the concentration of malt extract, (Lopez et al 2003). According to the literature, widely used carbon sources for lovastatin production are lactose, glycerol and glucose.…”
Section: Screening Of Substrates and Nutrientsmentioning
confidence: 99%
“…In the former case, monacolin K was found to inhibit cholesterol synthesis thus reducing hypolipidemia (Chairote et al 2008;Lee et al 2007), and lovastatin was found to reduce serum cholesterol and triglyceride (Panda et al 2009). The red pigment has been of increasing interest to the food industry because products are extracellular and water soluble making them easy to use.…”
Section: Introductionmentioning
confidence: 99%
“…A maximum lovastatin production of 2.83 mg/g fungal dry weight was obtained [18]. Effect of different substrates (sweet potato, potato, cassava and dioscorea) on monacolin-K production was investigated.…”
Section: Introductionmentioning
confidence: 99%